2014
DOI: 10.1371/journal.pone.0092540
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Pain Thresholds Increase after Preconditioning 1 Hz Repetitive Transcranial Magnetic Stimulation with Transcranial Direct Current Stimulation

Abstract: BackgroundThe primary motor cortex (M1) is an effective target of non-invasive cortical stimulation (NICS) for pain threshold modulation. It has been suggested that the initial level of cortical excitability of M1 plays a key role in the plastic effects of NICS.ObjectiveHere we investigate whether transcranial direct current stimulation (tDCS) primed 1 Hz repetitive transcranial magnetic stimulation (rTMS) modulates experimental pressure pain thresholds and if this is related to observed alterations in cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…So, our hypothesis, in which we assumed that c‐tDCS of these cortical sites increases P p Th, was not supported by the results. These findings are in line with the results of other c‐tDCS studies assessing the effects of M1 and S1 c‐tDCS on mechanical quantitative sensory testing parameters such as mechanical pain sensitivity, pressure pain threshold and wind‐up ratio (Rogalewski et al ., ; Bachmann et al ., ; Moloney & Witney, ). In contrast, Bachmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…So, our hypothesis, in which we assumed that c‐tDCS of these cortical sites increases P p Th, was not supported by the results. These findings are in line with the results of other c‐tDCS studies assessing the effects of M1 and S1 c‐tDCS on mechanical quantitative sensory testing parameters such as mechanical pain sensitivity, pressure pain threshold and wind‐up ratio (Rogalewski et al ., ; Bachmann et al ., ; Moloney & Witney, ). In contrast, Bachmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent fMRI studies showed that a-tDCS increases corticospinal excitability (CSE) of both local stimulated and distant areas, probably through interconnections between them (Meyerson et al, 1993 ; Lang et al, 2005 ). Literature indicates that tDCS induces CSE enhancement in M1, which could be used as a priming or stand-alone technique in therapeutic scenarios including improvement of motor function (Goodwill et al, 2013 ; Williams et al, 2013 ; Dutta et al, 2014 ; Filmer et al, 2014 ; Ludemann-Podubecka et al, 2014 ), motor learning (Kuo et al, 2008 ; Stagg and Nitsche, 2011 ; Zimerman et al, 2012 ; Karok and Witney, 2013 ; Vollmann et al, 2013 ; Meinzer et al, 2014 ; Parasuraman and Mckinley, 2014 ), and pain management (Bolognini et al, 2013 ; Bae et al, 2014 ; Foerster et al, 2015 ; Hagenacker et al, 2014 ; Moloney and Witney, 2014 ; Vaseghi et al, 2014 ; Wang et al, 2014 ; Zmigrod, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This manipulation of effects is based on the conceptual form of brain plasticity, "homeostatic plasticity" [82]. This protocol has been applied to the modulation of pain, and weak tDCS (1 mA) was used to "precondition" the brain to enhance the effects of subsequent stimulation via low-frequency rTMS (1 Hz) on the modulation of thermal sensation, thermal pain thresholds, and pressure pain thresholds, thereby producing a form of analgesia [83,84].…”
Section: Transcranial Direct Current Stimulation Priming Of Repetitivmentioning
confidence: 99%
“…This is best demonstrated in studies regarding application to the human motor cortex, where they attempt to direct the current to strictly follow the orientation of axons and/or dendrites in the induced electrical field [61]. Recent studies employ current flow models with defined montages [86] and use improved electrode positioning through the use of caps based on the international 10-20 positioning system [84].…”
Section: Dose Effects Of Neuromodulatory Interventionsmentioning
confidence: 99%